Lippincott Illustrated Reviews Biochemistry - Ritu Singh and others Ed; GOYAL (Rajeev) Ed; FERRIER (Denise R) Ed (Haryana Wolter Kluwer, 2024)
Lippincott® Illustrated Reviews: Biochemistry is the long-established go-to resource for mastering the essentials of biochemistry. This best- selling book helps students to quickly review, assimilate, and integrate large amounts of critical and complex information, with unparalleled illustrations that bring concepts to life. The second South Asian edition addresses the critical needs of undergraduate medical students, focusing on their ability to uity of biochemistry across all phases of MBBS.
Keywords: Indian competency Based Medical Curriculum; Immunology; Lipid; Medical Nutrition